2021
DOI: 10.6018/reifop.469921
|View full text |Cite
|
Sign up to set email alerts
|

Uso metodológico docente y rendimiento lector del alumnado: análisis fundamentado en PISA lectura 2018

Abstract: Las investigaciones en las que se vincula el rendimiento académico en lectura del alumnado y la utilización de modelos didácticos por parte del profesorado se caracterizan por el carácter exiguo y dispar de los resultados. Esta investigación analizó la influencia y relación entre la utilización metodológica que realizan 13119 docentes de España y el rendimiento académico del alumnado español en PISA lectura 2018. Para este propósito, se implementó un diseño de investigación descriptivo-correlacional en el que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For instance, Jaekel et al [22] found that a teacher's communication skills, ability to maintain good relationships with students, and time spent in the classroom are closely related to teaching quality ratings and student learning experiences. Rodríguez-García et al [23] discovered that a teacher's instructional method had a significant impact on students' reading scores, and that positive teaching styles were associated with higher achievement. Zhang et al [24] found that a teacher's professional characteristics had a significant impact on job satisfaction and that professional collaboration and teaching self-efficacy were key factors.…”
Section: Correlation Between Teacher Characteristics and Teaching Qua...mentioning
confidence: 99%
“…For instance, Jaekel et al [22] found that a teacher's communication skills, ability to maintain good relationships with students, and time spent in the classroom are closely related to teaching quality ratings and student learning experiences. Rodríguez-García et al [23] discovered that a teacher's instructional method had a significant impact on students' reading scores, and that positive teaching styles were associated with higher achievement. Zhang et al [24] found that a teacher's professional characteristics had a significant impact on job satisfaction and that professional collaboration and teaching self-efficacy were key factors.…”
Section: Correlation Between Teacher Characteristics and Teaching Qua...mentioning
confidence: 99%